Structure and content of the "demonstration of applied hand-to-hand combat techniques" section - Krutov , Vasyl; Kostiuchenko , Vasyl (Sportyvnyi Visnyk Prydniprovia, 2024)
Introduction. At the current stage of development, hand-to-hand combat is not only a dynamic and popular type of martial arts, but also one of the main areas of special physical training of military personnel and law enforcement officers, thanks to which the physical and moral-willed qualities necessary for the performance of official tasks are formed. A feature of competitive activities in hand-to-hand combat is the presence of two separate sections, duels and demonstrations of applied technique. Competitive activity in the section of demonstration of applied technique has its own characteristics and features that affect the construction of an effective training process. Today’s realities, the increased popularity of the section demonstration of applied technique in Ukraine and the world, high requirements for the level of technical preparation, fierce competition require industry specialists to optimize the structure and content of the educational and training process, develop new training programs, build a system of education-al and training process for participation in competitions in the section of demonstration of applied hand-to-hand combat technique. It is known that the effective management of the educational and training process is based on accurate knowledge of the specifics of the competitive activity of athletes. In connection with the above, the problem of researching the structure and content of the section on demonstration of applied hand-to-hand combat technique, determining its specifics and finding ways to further improve this direction, in accordance with the current trends in the development of the sport, becomes particularly relevant. The obtained information under the given conditions can be a fundamental basis for making changes in the training system of hand-to-hand combat athletes at various stages of multi-year improvement. The purpose of the study is on the basis of the analysis of normative documents and the competitive activity of the section demonstration of applied hand-to-hand combat technique, to determine the content and structure of this direction of competitive activity and outline ways of its optimization. Research methods: theoretical analysis and generalization of literary sources, pedagogical observation, questionnaires, methods of mathematical statistics. The results. In the course of the study, the specifics of competitive activity from the section demonstration of applied technique of hand-to-hand combat were studied in detail. Based on the analysis of the video materials, the structure and content in the section of demonstration of applied hand-to-hand combat technique were determined, models of the application of attack actions and defense against various types of threats were built, summarized data on the effectiveness of the use of throws and special pain techniques as a tool for solving situational tasks, recommendations for building of the training process in the section demonstration of applied technique were developed. Conclusions. In the process of research, the specifics of performing technical elements during competitive activities in the section of demonstration of applied hand-to-hand combat technique were determined. The theoretical and practical aspects of the scientific work presented above will be the basis for the theoretical justification and further improvement of the process of training young athletes in the direction of technique demonstration.